In High Places : A Novel - Hailey, Arthur (Bantam Books)
The Canadian prime minister's vital plan for union with the U.S. is upset by a modern man-without-a-country.
English Fiction.
Keywords: Cold War (1945-1989) -- Prime ministers -- Canada